Crescentic IgA nephropathy associated with pleural tuberculosis - Marques,Marta R (2019)
Crescentic IgA nephropathy represents an aggressive glomerular injury which can cause renal failure unless diagnosed and treated rapidly. There is currently no consensus on the most effective treatment strategy, although immunosuppressive drugs are usually used. Tuberculosis is rarely associated with glomerulonephritis and raises difficult questions about the safety and usefulness of immunosuppressive agents. We report a rare case of rapidly progressive renal failure associated with pleural tuberculosis in a 68-year-old man. The identification of crescents and fibrinoid necrosis in 12 out of 21 glomeruli and IgA deposits in the renal biopsy suggested the diagnosis of crescentic IgA nephropathy. Corticosteroids in combination with antituberculosis drugs were started with significant improvement in his general condition and cure of his pleural tuberculosis but without recovery of kidney function.